EFFECT OF GREEN LEAFY VEGETABLES (SPINACH AND SORREL) ON HAEMATOPOIESIS IN MALE WISTAR RATS (International Journal of Ayurveda and Pharma Research, 2015)
Spinach (Spinacia oleracea L.) is an edible flowering plant in the Amaranthaceae family and Sorrel (Hibiscus sabdariffa Linn.) is a shrub belonging to the Malvaceae family. It is thought of native to Asia (India to Malaysia) or Tropical Africa. The present study was aimed at investigating the effect of Green leafy vegetables (Spinach and Sorrel) on Hematopoiesis in male Wistar rats to know the effect on hematological parameters and oxidative stress in male rats. The study reveal that Spinach and sorrel leaves increased the RBC count, WBC count Hb%, and MCHC when compared control. The sorrel leaves exhibited prominent effect when compared to spinach leaves. However didnot exhibit prominent effect on platelet count. In addition, both the plant extracts showed significant effect on in decreased MDA levels when compared to control.